Case Report: endoscopic thyroidectomy via total areola approach in a six-year-old patient with thyroid follicular adenoma - Cai, Qingqing; Ke, Yifan; Li, Wenchao; Zhang, Peng; Wu, Jiezhong; Hu, Kunpeng (Frontiers in Pediatrics, 2025)
BackgroundEndoscopic thyroidectomy (ET) has become increasingly popular globally, but its application in young children remains largely unexplored. This study reports a 6-year-old girl with a neck mass who underwent ET via total areola approach.MethodsAfter ultrasonographic (ACR TI-RADS 4) and cytological (TBSRTC 4) confirmation, the patient underwent endoscopic right and isthmic thyroidectomy with inferior parathyroid auto-transplantation under general anesthesia. The procedure utilized 3 mm pediatric instruments, intraoperative neuromonitoring and near-infrared auto fluorescent parathyroid monitoring.ResultsThe procedure achieved complete resection with 215 min operative time and minimal blood loss. The pathological diagnosis was thyroid follicular adenoma. At 3-month follow-up, no complications and excellent cosmetic outcomes were observed.ConclusionET via total areola approach proves highly suitable for young children because of its safety and cosmetic advantages. Experienced surgeons, small-size special surgical instruments and auxiliary monitoring techniques are helpful to improve the safety of pediatric ET.